Pengaruh Penerapan Instruksi Kerja Alat Terhadap Keterampilan Penggunaan Alat Di Laboratorium Fakultas Tarbiyah Dan Keguruan Uin Sunan Ampel Surabaya - Reni Wulandari (UPT Laboratorium Terpadu, Universitas Diponegoro, 2019)
Permendikti No. 44 of 2015 explicitly states that college graduates must exceed knowledge achievements, general skills and special skills and attitudes. This study intends to find out how the application of work instruction tools in the laboratory, student skills in the laboratory and the effect of the application of tool work instructions on the skills of using the tools in the laboratory.The instrument used was in the form of an observation sheet with as many as 7 items of assessment with reliability = 0.615, the instruments of pre-test and post-test had been tested for validity.The results of the data analysis showed that students rarely applied tool work instructions when implementing practicum with a percentage of 56.52%, unskilled students in the use of tools with a percentage of 45.65%. Followed by data analysis for the influence of the application of tool work instructions on the skill use of tools in the laboratory. The z value was obtained at 5.769 and which was greater than the critical value z (1,645). This shows that there is the influence of the application of tool work instructions on the skillful use of laboratory equipment in the Tarbiyah Faculty and Sunan Ampel UIN Surabaya Teacher Training